(untitled) (Publicaciones en Ciencias y Tecnología, 2009)
Almeida, Amarilla and Baran studied the problem of cost-minimization multi-objective in short, medium and long term for the location of telephone exchanges in the city of Asuncion, Paraguay, determining the number of central and convenient location of these plants SPEAII using evolutionary algorithm. We propose in this paper to apply the evolutionary algorithm NSGAII the problem of locating telephone exchanges in Cabudare, Estado Lara, Venezuela; demonstrating that an option to address multiobjective problems.